Harmonization of Ethics of Compliance and Autonomy of Thinking in Islamic Boarding Schools in the Perspective of the Qur'an and Hadith - Ika Wahyuningsih; Aji Pangestu; Nur Hidayat (Program Pascasarjana Universitas Ibrahimy, 2025)
The restriction of the concept of compliance ethics in pesantren is often considered contradictory to the fulfillment of the right to freedom of opinion and the formation of autonomy to think in education. Therefore, this study aims to harmonize the traditional value of obedience in Islamic boarding schools with the need for critical thinking in the review of the Qur'an and Hadith. The type of research is qualitative, using data collection techniques in the form of interviews. The informants included the head of the boarding school and representatives of students from two Islamic boarding schools in the Sarang area, Rembang, Central Java, Indonesia. Data analysis includes; data collection, data condensation, data display, and conclusion drawing/verification. The results of the study found that learning practices and regulations that limit the autonomy of thinking, such as teachers not giving the opportunity to ask questions, strong ethics of obedience make students afraid of being assumed to be disrespectful when often giving criticism and suggestions, regulations that little consideration of students' proposals, seniority in Islamic boarding schools, and the character of caregivers who tend to be authoritarian. Responding to the ethics of obedience and autonomy of thinking, the Qur'an and Hadith provide an overview, including; for teachers to make mutually agreed learning contracts and use modern learning methods; For students, it is recommended to choose good teachers and caregivers, be patient and prejudiced against teachers and obey the teacher's orders while being kind. The autonomy to think and think must still maintain ethics, including speaking well and correctly so that it is not easily misunderstood and disturbs the comfort of others.